2020
DOI: 10.1029/2019ja027289
|View full text |Cite
|
Sign up to set email alerts
|

Do Statistical Models Capture the Dynamics of the Magnetopause During Sudden Magnetospheric Compressions?

Abstract: Under periods of strong solar wind driving, the magnetopause can become compressed, playing a significant role in draining electrons from the outer radiation belt. Also termed "magnetopause shadowing," this loss process has traditionally been attributed to a combination of magnetospheric compression and outward radial diffusion of electrons. However, the drift paths of relativistic electrons and the location of the magnetopause are usually calculated from statistical models and, as such, may not represent the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 87 publications
(165 reference statements)
5
50
0
Order By: Relevance
“…In Figure 5, times when the spacecraft locator (Staples et al, 2020) predicted magnetopause crossings are marked with red vertical lines (Figure 2). The local B magnitude average near the identified magnetopause crossings gives an indication that the magnetopause location is well reproduced with the simulation.…”
Section: Magnetospheric Boundary Motionmentioning
confidence: 99%
“…In Figure 5, times when the spacecraft locator (Staples et al, 2020) predicted magnetopause crossings are marked with red vertical lines (Figure 2). The local B magnitude average near the identified magnetopause crossings gives an indication that the magnetopause location is well reproduced with the simulation.…”
Section: Magnetospheric Boundary Motionmentioning
confidence: 99%
“…These empirical studies revealed additional influences from the Interplanetary Magnetic Field (IMF) orientation, which modulates magnetic reconnection and the Dungey (1961) cycle, solar wind magnetic pressure and dipole tilt (Lin et al., 2010), IMF cone angle (Merka et al., 2003), and ionospheric conductivity and solar wind velocity (Němeček et al., 2016). These best‐fit models are, however, static and can deviate when compared to specific observations (Samsonov et al., 2020), particularly during extreme solar wind conditions with discrepancies of >1normalRE observed when located less than 8normalRE upstream (Staples et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The dawn-dusk asymmetries observed might be explained by similar dawn-dusk asymmetries in the magnetosphere (Haaland et al, 2017;Staples et al, 2020;Walsh et al, 2014). As we have excluded the lower energy particles from this portion of analysis, we do not expect this asymmetry to be primarily due to E × B drift, since the curvature and gradient drifts are energy dependent and hence will dominate over the electric field drift (though some recent works have shown that the electric field may still contribute: Sillanpää et al, 2017;Califf et al, 2017).…”
Section: Discussionmentioning
confidence: 76%
“…This causes the electrons to follow the field and drift further out because of the gradient drift experienced. The sense of the dawn-dusk asymmetry suggests it is not simply the result of the algorithm identifying the magnetopause rather than the OBORB, the magnetopause can be compressed to below 8 R E , but this happens much more frequently at dawn than dusk (Staples et al, 2020). Whilst there may be some contamination of the data due to sampling the magnetopause or solar wind, we infer that this is negligible, since electron populations (and hence their distribution functions) are very different.…”
Section: Discussionmentioning
confidence: 86%